Photoactivatable prodrugs of butyric acid based on new coumarin fused oxazole heterocycles. (February 2017) - Soares, Ana M.S.; Hungerford, Graham; Costa, Susana P.G.; Gonçalves, M. Sameiro T.
Abstract: New coumarin fused oxazoles were investigated as photosensitive units for carboxylic acid groups using butyric acid as a model compound. 6-Oxo-6 H -benzopyrano[6, 7- d ]oxazol-8-yl)methyl derivatives possessing various (hetero)aromatic substituents at position 2 of the heterocyclic system were used in the synthesis of ester conjugates of butyric acid. Photolysis at selected wavelengths in methanol/HEPES buffer (80:20) solutions, monitored by HPLC/UV and 1 H NMR, resulted in the complete release of butyric acid. The shorter irradiation times for cleavage at longer wavelengths occurred for the conjugate with a 4-oxo-4 H -benzopyran-2-yl substituent and thus (6-oxo-2-(4-oxo-4 H -benzopyran-2-yl)-6 H -benzopyrano[6, 7- d ]oxazol-8-yl)methyl has potential as a candidate photosensitive moiety for butyric acid prodrugs. Graphical abstract: Highlights: Chloromethylated coumarin fused oxazoles were used in the derivatisation of butyric acid, as model carboxylic acid drug. The new seven cages, 6-oxo-6 H -benzopyrano[6, 7- d ]oxazol-8-yl)methyl groups, revealed to be photo-responsive upon irradiation. Photolysis of the cages resulted in the complete release of butyric acid. The coumarin fused oxazole with phenyl or chromone substituents are especially pertinent for bioapplications. This study shows new promising alternative moieties for the development of photoactivable fluorescent butyric acid prodrugs.